Journeying together to Evangelize: A Look at the Synodal Church of Pope Francis - Palakeel, Joseph Scaria (Asian Horizons, 2020)
Pope Francis believes that Church of the third millennium must be Synodal, an ‘inverted pyramid.’ This prophetic and courageous step in Church reform by Pope Francis is in close continuity with the ancient and rich synodal tradition of the Early Church and the unfinished agenda of the Second Vatican Council. In a hierarchical Church Pope and Bishops are privileged listeners to the Holy Spirit and are mandated to teach the people of God, whereas in the Synodal church the magisterium listens to the Holy Spirit speaking to them through the people of God (LG 12) as well and, thus, includes a two-way process of common listening to the Spirit and communal discernment (sensus fidei) by the entire people of God who journey together to evangelize and bring about the Kingdom of God. It is a revolutionary move towards de-centralisation of the Catholic church which opens up fresh questions about the role of pope and papal primacy, the juridical status of the local and regional bishops’ conferences and the participation of the laity, especially women, in doctrinal formulation and ecclesiastical administration. In this article, I seek to outline and explain Pope Francis’ vision of a synodal church based on his own teachings.